Analisa Pengetahuan Masyarakat UKM terhadap Penggunaan Strategi Digital Marketing di Desa Ciherang Pondok Kec. Caringin Berdasarkan Perspektif Ekonomi Islam - Ardi Gusnadi Awaludin; Fariddudin Malikur Rahmat (ALIF, 2023)
The purpose of this research is to analyze people's knowledge and skills about digital marketing, especially in social media platformsÂ for Small and Medium Enterprises (UKM) actors who can increase sales and profits. In this study the authors used a qualitative descriptive research methodology. The object of this research is the SMEs in Ciherang Pondok Village, Caringin Subdistrict.Â The results of this study indicate that there are still many factors that hinder the people of Ciherang Pondok Village from using digital marketing. Marketing through online can increase and marketing profits. From the results of the study it was found that only a small proportion actively used social media as a means of promotion, the use of accounts was not separated between personal and shops. This also causes a lack of customer convenience in visiting the store. The reason for this is due to the lack of community guidance regarding the understanding and use of technology, especially in digital marketing techniques. Even though many people show great interest in using social media for shopping, because it is practical in its use, so do sellers who show an interest in using digital marketing but are hampered by their knowledge